A more defective substrate leads to a less defective passive layer: Enhancing the mechanical strength, corrosion resistance and anti-inflammatory response of the low-modulus Ti-45Nb alloy by grain refinement. (May 2021) - Hu, Nan; Xie, Lingxia; Liao, Qing; Gao, Ang; Zheng, Yanyan; Pan, Haobo; Tong, Liping; Yang, Dazhi; Gao, Nong; Starink, Marco J.; Chu, Paul K.; Wang, Huaiyu
Abstract: Orthopedic and dental implants made of β-type Ti alloys have low elastic modulus which can better relieve the stress shielding effects after surgical implantation. Nevertheless, clinical application of β-type Ti alloys is hampered by the insufficient mechanical strength and gradual release of pro-inflammatory metallic ions under physiological conditions. In this study, the β-type Ti-45Nb alloy is subjected to high-pressure torsion (HPT) processing to refine the grain size. After HPT processing, the tensile strength increases from 370 MPa to 658 MPa due to grain boundary strengthening and at the same time, the favorable elastic modulus is maintained at a low level of 61-72 GPa because the single β-phase is preserved during grain refinement. More grain boundaries decrease the work function and facilitate the formation of thicker and less defective passive films leading to better corrosion resistance. In addition, more rapid repair of the passive layer mitigates release of metallic ions from the alloy and consequently, the inflammatory response is suppressed. The results reveal a strategy to simultaneously improve the mechanical and biological properties of metallic implant materials for orthopedics and dentistry. Statement of significance: The low modulus Ti-45Nb alloy is promising in addressing the complication of stress shielding induced by biomedical Ti-based materials with too-high elastic modulus. However, its insufficient strength hampers its clinical application, and traditional strengthening via heat treatments will compromise the low elastic modulus. In the current study, we enhanced the ultimate tensile strength of Ti-45Nb from 370 MPa to 658 MPa through grain-refinement strengthening, while the elastic modulus was maintained at a low value (61-72 GPa). Moreover, substrate grain-refinement has been proved to improve the corrosion resistance of Ti-45Nb with reduced inflammatory response both in vitro and in vivo . A relationship between the substrate microstructure and the surface passive layer has been established to explain the beneficial effects of substrate grain-refinement. Graphical abstract: Image, graphical abstract